Cotas nas universidades e aprendizado escolar: modelo teórico e evidências empíricas - Zylberstajn, Eduardo (2010)
This work studies the consequences of affirmative action policies, specifically color-oriented quotas, on the learning of pupils during school. The literature on the subject is controversial; there are authors who argue theoretical and empirically that incentives to human capital accumulation decrease with this sort of policy, but there are also those who claim the opposite. In Brazil, there are only a few studies, especially theoretical ones. The empirical evidence are typically restricted to one or two states and this might be one of the reasons for these differences. The theoretical model presented in this work spells out conditions for the two situations (increase or decrease the effort) occur, and shows that the consequences of quotas are heterogeneous and depend on the students’ characteristics. The empirical evidence presented seems to corroborate that possibility, since the academic outcomes of black and white students may increase or decrease.